2007
DOI: 10.1111/j.1524-475x.2007.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and physiologic evidence for biofilm‐associated wound colonization in vivo

Abstract: A biofilm is a collection of microbial cells that are attached to a surface and embedded in a self-produced extrapolymeric substance. The understanding of the biofilm phenotype is important in the understanding of bacteria in vitro but it has been difficult to translate biofilm science to the clinical setting. More recently, preliminary criteria for defining biofilm associated diseases have been proposed and the purpose of this study was to create a biofilm-associated wound model based on these criteria. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
259
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(271 citation statements)
references
References 18 publications
9
259
1
2
Order By: Relevance
“…Moreover, it has been shown that in 45 of 915 samples, Fusarium spp. formed biofilms in chronic wound infections [26].…”
Section: Fusarium Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that in 45 of 915 samples, Fusarium spp. formed biofilms in chronic wound infections [26].…”
Section: Fusarium Biofilmsmentioning
confidence: 99%
“…[22]. It was also reported that as a result of low metabolic activities of biofilms, micro-organisms in biofilm forms are more difficult to eliminate with conventional antimicrobial agents than planktonic forms [26].…”
Section: Fusarium Biofilmsmentioning
confidence: 99%
“…24 Studies on animals, including rats, mice, rabbits, and pigs, have mostly addressed short-term acute-phase processes ranging between 2 and 26 days of infection (Table 1). 7,10,[25][26][27][28][29] Such approaches are of limited value as they fail to capture the long-term interplay between the host and biofilm, which has a significant bearing of the wound microenvironment at the site of the infection. 17 This article aims to concisely and critically review the various in vitro and in vivo models used for the study of biofilm infections of wounds with specific emphasis on the preclinical porcine model of chronic infections (duration of 8 weeks) recently reported by our laboratory.…”
Section: Models Of Biofilm Infectionsmentioning
confidence: 99%
“…45 Additionally and importantly, the human immune system has a higher similarity to the porcine immune system compared to rats or mice, making it a better suited model for studies on the host interactions that are integral to the complexities of the pathological biofilm in wound infections. 46 Davis et al 25 developed a porcine wound biofilm model, where partial-thickness wounds in pigs were infected with S. aureus. Using electron microscopy, the presence of biofilm matrix was established.…”
Section: Porcine Modelsmentioning
confidence: 99%
“…Together, these micro-organisms form a multispecies biofilm construct that protects them from antimicrobial therapy and the patient's immune system (Price et al, 2009;Attinger & Wolcott, 2012). Biofilm growth and its persistence within wounds have recently been suggested as contributing factors to impaired healing (Rhoads et al, 2007;Bjarnsholt et al, 2008;Davis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%